Weak agency and preferences for participatory democracy: discourses of Spanish people in positions of socioeconomic disadvantage. Issue 6 (18th August 2022) - García-Espín, Patricia
ABSTRACT: Recent studies exploring public opinion on participatory democracy show that disadvantaged social groups tend to hold favourable views on participatory processes. At the same time, research has also found that these groups frequently express feelings of weak agency and lack of competence to make valuable contributions to political processes. How then is support for democratic participation to be understood, if people see themselves as unskilled and incapable agents? To address this question, a series of focus groups were conducted with young, middle-aged, and older Spanish adults in situations of socioeconomic disadvantage. Like other studies, the analysis found that the participants had positive views of participatory reforms, but this was modified by low levels of personal and collective agency (internal and external efficacy and horizontal mistrust). While some scholars argue that such ambivalence is coherent with populism, the analysis suggests that many participants (particularly younger and middle-aged adults) are keenly appreciative of the complexity of such proposals and that negativity relates to the implementation of participative processes without genuine redistribution of knowledge and power, as well as a lack of mechanisms to guarantee responsiveness and commitment to bottom-up democracy.